2023
DOI: 10.3389/fendo.2023.1145111
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding on pathogenesis and effective treatment of glycogen storage disease type Ib with empagliflozin: new insights coming from diabetes for its potential implications in other metabolic disorders

Abstract: Glycogen storage type Ib (GSDIb) is a rare inborn error of metabolism caused by glucose-6-phosphate transporter (G6PT, SLC37A4) deficiency. G6PT defect results in excessive accumulation of glycogen and fat in the liver, kidney, and intestinal mucosa and into both glycogenolysis and gluconeogenesis impairment. Clinical features include hepatomegaly, hypoglycemia, lactic acidemia, hyperuricemia, hyperlipidemia, and growth retardation. Long-term complications are liver adenoma, hepatocarcinoma, nephropathy and os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 147 publications
(155 reference statements)
0
1
0
Order By: Relevance
“…Recently, after Wortmann et al reported the use of empagliflozin for treating neutropenia and neutrophil dysfunction in GSD-Ib patients 18 , more than 230 adult or paediatric patients with GSD-Ib who received empagliflozin have been reported in more than 20 pieces of literature, including two international questionnaire studies 20 , 31 and some case reports 21 , 32 36 . The efficacy in these studies was assessed by clinical symptoms and the PCDAI 6 , 28 , empagliflozin has been recommended for the treatment of neutrophil dysfunction in GDS-Ib patients with or without IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, after Wortmann et al reported the use of empagliflozin for treating neutropenia and neutrophil dysfunction in GSD-Ib patients 18 , more than 230 adult or paediatric patients with GSD-Ib who received empagliflozin have been reported in more than 20 pieces of literature, including two international questionnaire studies 20 , 31 and some case reports 21 , 32 36 . The efficacy in these studies was assessed by clinical symptoms and the PCDAI 6 , 28 , empagliflozin has been recommended for the treatment of neutrophil dysfunction in GDS-Ib patients with or without IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Диетотерапия при БНГ Ia и БНГ Ib идентична, но последним в связи с предрасположенностью к ВЗК необходимы дополнительные ограничения. Отказ от голодания -это первая линия лечения путем частого употребления высокоуглеводной диеты с низким содержанием жира, дополненной сырым кукурузным крахмалом [2,12]. На первом году жизни ночные приемы пищи могут быть заменены непрерывным энтеральным питанием через назогастральный зонд или гастростому.…”
Section: современные методы лечения бнг Ib типа аспекты питанияunclassified
“…Эмпаглифлозин потенциально может быть использован также у пациентов с БНГ Ia с целью улучшения метаболических показателей, профилактики митохондриального стресса, инсулинорезистентности, неалкогольной жировой болезни печени (НАЖБП) и нефропатии [12].…”
Section: эмпаглифлозинunclassified
See 1 more Smart Citation
“…Other drugs that inhibit bone resorption include monoclonal antibodies targeting the receptor activator of nuclear factor-κB ligand (RANKL), calcitonin, and estrogen 9 . Bone formation-promoting drugs, as well as bifunctional drugs such as parathyroid hormone analogs, active vitamin D and its analogs, vitamin K, and romosozumab, have been widely recognized for clinical application 10 . However, systemic therapy has limitations, such as the need for treatment continuation for more than one year and the risk of osteoporotic fractures before and after discontinuation of treatment.…”
Section: Introductionmentioning
confidence: 99%